2007
DOI: 10.1007/s10464-007-9156-6
|View full text |Cite
|
Sign up to set email alerts
|

Community Resilience as a Metaphor, Theory, Set of Capacities, and Strategy for Disaster Readiness

Abstract: Communities have the potential to function effectively and adapt successfully in the aftermath of disasters. Drawing upon literatures in several disciplines, we present a theory of resilience that encompasses contemporary understandings of stress, adaptation, wellness, and resource dynamics. Community resilience is a process linking a network of adaptive capacities (resources with dynamic attributes) to adaptation after a disturbance or adversity. Community adaptation is manifest in population wellness, define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
3,186
0
143

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,765 publications
(3,648 citation statements)
references
References 114 publications
72
3,186
0
143
Order By: Relevance
“…Positive emotions are seen as active ingredients within trait resilience, which reduce the risk of depression and promote thriving (Fredrickson et al, 2003). In other studies, emotional resilience has been used as a concept to imply the flexible use of emotional resources for adapting to adversity (Waugh, Fredrickson, & Taylor, 2008) or as the process linking resources (adaptive capacities) to outcomes (adaptation) (Norris, Stevens, Pfefferbaum, Wyche, & Pfefferbaum, 2008). Researchers using this concept view resilience as a process or force that drives a person to grow through adversity and disruption (Jacelon, 1997;Richardson & Waite, 2002;Richardson, 2002).…”
Section: Current Conceptualisations Of Resiliencementioning
confidence: 99%
“…Positive emotions are seen as active ingredients within trait resilience, which reduce the risk of depression and promote thriving (Fredrickson et al, 2003). In other studies, emotional resilience has been used as a concept to imply the flexible use of emotional resources for adapting to adversity (Waugh, Fredrickson, & Taylor, 2008) or as the process linking resources (adaptive capacities) to outcomes (adaptation) (Norris, Stevens, Pfefferbaum, Wyche, & Pfefferbaum, 2008). Researchers using this concept view resilience as a process or force that drives a person to grow through adversity and disruption (Jacelon, 1997;Richardson & Waite, 2002;Richardson, 2002).…”
Section: Current Conceptualisations Of Resiliencementioning
confidence: 99%
“…In a larger contextual framework, it is evident that building collective resilience is a key factor in preventing adolescent depression, which includes addressing social inequality, creating organisational collaboration, protecting social support initiatives and engaging adolescents in mitigation of the effects of climate change (80). It has been suggested that talking about the psychological impact of climate change in general will help to better process and accept potentially overwhelming climate information and thus prevent more longstanding climate-related depression (74).…”
Section: Implications For Novel Treatment Strategiesmentioning
confidence: 99%
“…Socially, natural disasters can often strengthen social ties in the community by bringing residents together for a common cause, and for recovery and rebuilding (Sattler et al, 1995). However, emerging evidence from the literature on post-disaster consequences shows that existing ties can be disrupted when residents leave communities either temporarily or permanently when their homes are damaged (Norris et al, 2008). The recovery phase is a process of competition and conflict that impacts individuals unequally and may have additional effects for communities.…”
Section: The Impact Of Disasters On Individualsmentioning
confidence: 99%
“…However, understanding whether this increase remained 13 six months after the disaster hit will contribute to a better understanding of how perceptions of one's community are affected by sudden physical and social environmental change. Norris et al (2008) argue that collective efficacy and individual perceptions of cohesion and social control are intrinsically related to community and individual resilience. Therefore, understanding how these perceptions change as a result of a disaster is critical for understanding the recovery process and whether these are the same vulnerable groups that will struggle in future disasters.…”
Section: The Impact Of Disasters On Individualsmentioning
confidence: 99%
See 1 more Smart Citation